Application of PROMETHEE Method to Support the Best Flourist - Ni Kadek Shely Prastikayani; Ni Ketut Maria Suryani; Ni Luh Sri Deviyanti; I Gede Iwan Sudipa; I Nyoman Tri Anindia Putra (BIOS: Jurnal Informatika dan Sains, 2025)
Determining the best flower shop in the INSTIKI campus area is a challenge because it involves various criteria that affect each other. This research applies the PROMETHEE (Preference Ranking Organization Method for Enrichment Evaluations) method, a multicriteria decision-making method, to broadcast three alternative flower shops based on ten criteria, namely accessibility, price, product quality, product availability, service, store reputation, promotions and discounts, availability, operating hours, and transaction security. Data were obtained from a survey to university students. The analysis results show that Poppy Florist Bali is the best choice with the highest net flow value, followed by Flora Flower Boutique and Anya Florist. The PROMETHEE method is proven to provide a transparent, structured, and effective approach in supporting strategic decision making, thus providing relevant recommendations for flower shop business development.